Pengaruh Laba Rugi, Opini Audit Dan Lamanya Listing Terhadap Audit Delay - Ade Sri Ulita; Agus Nisfur Romdioni (Musamus University, 2019)
Criteria set out aims to find out how much it affects the audit delay. Income is measured using profit or loss incurred by the company, audit opinion is measured by looking at the auditor's opinion on the fairness of the company's financial statements, the length of the company listing is measured by the number of days listed in the Stock Exchange Indonesia while audit delay is measured by the number of days the company delayed audited financial report in the Indonesia Stock Exchange. The research method used is multiple regression analysis with purposive sampling method with sample of companies listed on the Indonesia Stock Exchange mining sector. The results showed that the audit delay was influenced by the income and the auditor's opinion and the duration of the listing does not affect the occurrence of audit delay while simultaneously, the profit or loss of the company, Audit opinion and the duration of influential Against Auidt delay.